Facile synthesis strategy for phthalocyanine-titanium dioxide/multi-walled carbon nanotube/poly(3,4-ethylenedioxythiophene) ternary composite electrodes via one-step electrochemical method for supercapacitor applications - Artar, Emirhan; Arvas, Melih Besir; Gorduk, Ozge; Gorduk, Semih; Sahin, Yucel (ELSEVIER SCIENCE SA, 2023)
Recent advances in the construction of ternary composite electrodes have revealed new strategies for energy storage applications. For energy storage applications, supercapacitors have attracted significant attention owing to their fascinating electrochemical performance and combining advantages. In this study, a facile and one-step electrochemical method was used for synthesis of metallo phthalocyanine-titanium dioxide/functionalized-multiwalled carbon nanotube/poly(3,4-ethylenedioxythiophene) ternary composite on pencil graphite electrode (MPc-TiO2/f-MWCNT/PEDOT/PGE) with high specific capacitance and long cycle life for supercapacitors. In this context, ZnPc-TiO2/f-MWCNT/PEDOT/PGE and NiPc-TiO2/f-MWCNT/PEDOT/PGE materials were produced by cyclic voltammetry method for the first time in the literature. The results of this study have revealed that multiwalled carbon nanotube/poly(3,4-ethylenedioxythiophene) when functionalized with metallo phthalocyanine-titanium dioxide shows higher specific capacitance than multiwalled carbon nanotube/poly(3,4-ethylenedioxythiophene) forms. Among the modified electrodes containing ternary composite, ZnPc-TiO2/f-MWCNT/PEDOT/PGE electrode showed highest specific capacitance (395.98 F.g  1) value. Additionally, both ZnPc-TiO2/f-MWCNT/PEDOT/PGE and NiPc-TiO2/f-MWCNT/PEDOT/PGE have long-cycle life and have highly maintained their capacitance after 1000 charge/discharge cycles. The developed simple and efficient strategy in this work is the first report on the electrochemical synthesis of MPc-TiO2/f-MWCNT/PEDOT, which opens up new perspective for synthesizing electrode materials for energy storage applications.
Keywords: Phthalocyanine; Titanium dioxide; Poly(3; 4-ethylenedioxythiophene); Multi-walled carbon nanotube; Supercapacitor; CONDUCTING-POLYMER; PHOTOCATALYTIC PROPERTIES; NANOTUBE COMPOSITE; HYBRID MATERIAL; PERFORMANCE; ARRAYS; OXIDE; NANOCOMPOSITE; NANOHYBRID; PROGRESS; Materials Science; Physics; Polymer Science